Regulatory Reform : Integrating Paradigms - de la Torre, Augusto; Ize, Alain (2012)
The Subprime crisis largely resulted from failures to internalize systemic risk evenly across financial intermediaries and recognize the implications of Knightian uncertainty and mood swings. A successful reform of prudential regulation will need to integrate more harmoniously the three paradigms of moral hazard, externalities, and uncertainty. This is a tall order because each paradigm leads to different and often inconsistent regulatory implications. Moreover, efforts to address the central problem under one paradigm can make the problems under the others worse. To avoid regulatory arbitrage and ensure that externalities are uniformly internalized, all prudentially regulated intermediaries should be subjected to the same capital adequacy requirements, and unregulated intermediaries should be financed only by regulated intermediaries. Reflecting the importance of uncertainty, the new regulatory architecture will also need to rely less on markets and more on "holistic" supervision, and incorporate countercyclical norms that can be adjusted in light of changing circumstances.